IKHTIAR MENYEMAI MINAT DAN BAKAT SANTRI PONDOK PESANTREN DARUL MUTAQIEN 1 CADAS DI BIDANG KEWIRAUSAHAAN PADA ERA DIGITAL - Priyanto, Yuwono; Suryani, Ela (Jurnal Serina Abdimas, 2023)
The activities of the Student Creativity Program (PKM) are carried out in the Darul Muttaqien 1 campsite to explore the interests and talents of the students. Through a profound understanding of their interests and talents, the hostel invites participants to develop their potential in finding creative ideas.This research uses qualitative methods with a normative legal research approach. Data is collected through interviews and surveys to identify interests and talents that can be developed in the business world, especially in the growing digital age.The results of the research showed the need to encourage the interests and talents of centers in starting and developing in the digital age. Centers face the challenge of continuing to learn and understand consumers as well as the current trends in the digital world.In the advanced digital age, leaders need to develop creative ideas to stay relevant and not be left behind by emerging trends. Following popular trends, understanding consumer behavior, and mastering digital marketing strategies are key to success in entrepreneurship in the digital age.In an effort to develop the talents and interests of the attendants, the Darul Muttaqien 1 training house is committed to providing the necessary support and training. Thus, leaders are expected to have a courageous and confident mind in developing their potential for success in entrepreneurship in the increasingly advanced digital age.